The Effect of Foot Massage Therapy Using Lavender Oil on Lowering Blood Pressure in Hypertensive Patients at Kabila Health Center - Cindy Claudia Ahmad; Nanang Roswita Paramata; Andi Mursyidah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypertension is a chronic condition with systolic blood pressure ?140 mmHg and/or diastole ?90 mmHg that is at risk of cardiovascular complications. One of the nonpharmacological therapies such as foot massage using lavender oil is an important alternative that can improve relaxation and modulate the autonomic nervous system. This study aims to analyze the effect of this therapy on reducing blood pressure of hypertensive patients at the Kabila Health Center. The research design used, which was quasi-experimental with two groups, was used on 30 respondents (15 interventions and 15 controls) who were selected through accidental sampling techniques. The research instruments included SOP foot massage and blood pressure measurement using a digital sphygmomanometer. Data analysis was carried out by Wilcoxon test and paired t-test for comparison within groups, as well as independent sample t-test for comparison between groups. The results showed a significant decrease in systolic and diastolic blood pressure in the intervention group p = 0.001 (p < 0.05) with the mean systole decreasing from 156.20 to 150.20 mmHg and the median diastole from 92 to 81 mmHg. In the control group, there was no significant change in systol p = 0.096 (p > 0.05) and diastol p = 0.230 (p > 0.05). Significant differences between groups were found for systol p = 0.024 (p < 0.05) and diastol p = 0.000 (p < 0.05). The conclusion that foot massage therapy using lavender oil had a significant effect on lowering the blood pressure of hypertensive patients at the Kabila Health Center